The Role of Quality of Academic Information Systems and Facilities on Student Loyalty - Milka Rositi Sianipar; Efendy Pakpahan; Putranto Manalu (Universitas Muhammadiyah Yogyakarta, 2022)
Abstract: The growth of quality standards, as well as, higher student demands has implications for higher education to improve service quality to be able to provide satisfaction that leads to increased student loyalty.Research aims: This study determines the effect of academic information systems and facilities on student loyalty at the Faculty of Economics, Universitas Prima Indonesia through satisfaction as an integral variable.Design/Methodology/Approach: Data analysis using path analysis, and feasibility test of the model with the Smartpls 3.0 program. The population in this study were all 5th term students of Management Undergraduate Degree and Accounting Undergraduate Degree. The number of samples was determined using the Krejcie-Morgan table so that 291 people were selected.Research findings: The results showed that the academic information system had a significant positive effect on student loyalty through satisfaction, so that the satisfaction variable mediates the academic information system on student loyalty (t-statistic = 2.131 ( t-table): p-value = 0.034). Likewise, the effect of facilities on student loyalty through satisfaction as an intervening variable that shows a significant value (t-statistic = 2,220 ( t-table): p-value = 0.027).Theoretical contribution/Originality:. The novelty of this research is that increasing student loyalty can be done by improving academic information system services and adequate campus facilities.Practitioner/Policy implication: The university management must provide quality facilities and infrastructure to increase student loyalty.